2020
DOI: 10.1016/j.cell.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Burden Is Controlled by Mural Cell-β3-Integrin Regulated Crosstalk with Tumor Cells

Abstract: Highlights d Low mural-b3-integrin in tumor BVs is associated with poor prognosis in human cancers d Mural-b3-integrin loss enhances tumor growth in tumor models without vascular changes d Mural-b3-integrin loss upregulates FAK-p-HGFR-p-Akt-p-p65-driven cytokine production d Mural cell-derived CCL2 activates MEK1-ROCK2-dependent tumor growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 76 publications
4
52
0
Order By: Relevance
“…Recently, Wong et al . showed how tumor growth also depends on novel integrin-dependent non-canonical function of pericytes that act as paracrine sources of tumor trophic factors 76 . Indeed, in different human cancers, the simple lack of β3 integrin in blood vessel mural cells correlates with a larger tumor size and clinically more aggressive phenotype 76 .…”
Section: Integrin In the Context Of Cancer Progression And Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wong et al . showed how tumor growth also depends on novel integrin-dependent non-canonical function of pericytes that act as paracrine sources of tumor trophic factors 76 . Indeed, in different human cancers, the simple lack of β3 integrin in blood vessel mural cells correlates with a larger tumor size and clinically more aggressive phenotype 76 .…”
Section: Integrin In the Context Of Cancer Progression And Therapymentioning
confidence: 99%
“…showed how tumor growth also depends on novel integrin-dependent non-canonical function of pericytes that act as paracrine sources of tumor trophic factors 76 . Indeed, in different human cancers, the simple lack of β3 integrin in blood vessel mural cells correlates with a larger tumor size and clinically more aggressive phenotype 76 . Mechanistically, the absence of β3 integrin in pericytes, though not altering blood vessel number and function, upregulates the FAK-MET-AKT-NFKB–driven production of the cytokine CCL2 that in turn sustains tumor growth in a CCR2 receptor–dependent manner 76 .…”
Section: Integrin In the Context Of Cancer Progression And Therapymentioning
confidence: 99%
“…Our data demonstrate that FAK-Y861F pericytes decrease tumour burden, at least in part, by directly affecting tumour cell apoptosis, and call for further consideration of the role of tumour pericytes in the direct control of tumour growth, in addition to their effects on vessel stabilisation. Indeed, we have recently shown that pericytes play a central role in the control of primary tumour growth, through cross-talk with multiple cell types in the tumour microenvironment [19,20]. FAK is upregulated in many cancer types and is currently being targeted as a potential anti-cancer agent because of its essential roles in tumour growth and angiogenesis [12,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst FAK has been studied extensively in endothelial cells, the function of FAK in pericytes during tumour growth and angiogenesis is starting to emerge, with loss of pericyte FAK enhancing tumour angiogenesis [19]. Given that pericytes are an important cell type in the regulation of tumour growth and paracrine signalling [20][21][22], here we have examined the role of FAK point mutations in pericytes during pathological angiogenesis. Specifically, we have examined the effect of non-phosphorylatable mutations of tyrosines 397 and 861 (Y397F and Y861F) -FAK residues using pericyte-specific FAK Y397F/Y397F and FAK Y861F/ Y861F mice.…”
Section: Introductionmentioning
confidence: 99%
“…several disorders, from hypertension (Rodríguez-Vita et al, 2005a) and atherosclerosis (Rodríguez-Vita et al, 2008) to cancer (Wong et al, 2020) and more recently even COVID-19 (He et al, 2020). Whereas capillaries are mostly covered by pericytes, larger blood vessels contain VSCMs in the vessel wall.…”
mentioning
confidence: 99%